2013
DOI: 10.1161/circresaha.113.301780
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a Regulates Pathological and Physiological Angiogenesis by Targeting BMP/SMAD1 Signaling

Abstract: Rationale The rapid induction and orchestration of new blood vessels are critical for tissue repair in response to injury, such as myocardial infarction, and for physiological angiogenic responses, such as embryonic development and exercise. Objective We aimed to identify and characterize microRNAs (miR) that regulate pathological and physiological angiogenesis. Methods and Results We show that miR-26a regulates pathological and physiological angiogenesis by targeting endothelial cell (EC) bone morphogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
163
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 54 publications
(61 reference statements)
5
163
1
Order By: Relevance
“…MiR‐26a can be down‐regulated by pro‐angiogenic stimuli such as VEGF or TNF, which can inhibit angiogenesis via targeting the SMAD1–Id1–p21 WAF/CIP1 /p27 signalling axis in ECs 116. Importantly, a study showed that the inhibition of miR‐26a can rapidly enhance angiogenesis and decrease AMI size with improved heart function in a mouse model of AMI, while overexpression miR‐26a leads to the opposite results 117. Mechanically, miR‐26a represses VEGF signalling via directly targeting NgBR, and therefore inhibit angiogenesis by performing proliferation, migration and tube formation in HUVECs 118.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
See 2 more Smart Citations
“…MiR‐26a can be down‐regulated by pro‐angiogenic stimuli such as VEGF or TNF, which can inhibit angiogenesis via targeting the SMAD1–Id1–p21 WAF/CIP1 /p27 signalling axis in ECs 116. Importantly, a study showed that the inhibition of miR‐26a can rapidly enhance angiogenesis and decrease AMI size with improved heart function in a mouse model of AMI, while overexpression miR‐26a leads to the opposite results 117. Mechanically, miR‐26a represses VEGF signalling via directly targeting NgBR, and therefore inhibit angiogenesis by performing proliferation, migration and tube formation in HUVECs 118.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…Moreover, plasma miR‐26a is up‐regulated in a model of AMI in mice and in human beings with ACS 117. Interestingly, recent discoveries showed that circulating miR‐214 was up‐regulated in the early phase after AMI but then gradually decreased to near normal levels 163.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these two-stage, cell-free, miR-26a loaded scaffolds demonstrated significantly enhanced bone regeneration in critical-sized calvarial bone defects in both healthy and osteoporotic mice after only 8 weeks. miR-26a has previously been shown to regulate suppression of connective tissue growth factor, [147] angiogenesisthrough bone morphogenetic protein 2 (BMP2)/drosophila mothers against decapentaplegic protein (SMAD) signaling -in endothelial cells, [148] and atherosclerosis via a EphA2/p38 MAPK/vascular endothelial growth factor (VEGF) pathway. [149] Work by Luzi et al [150] has however pointed at a complex role for the miR-26a::SMAD1 match in human ASCs osteogenesis.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 99%
“…6 miR-26a is abundant in cardiac and other tissues and promotes vascular smooth muscle cell proliferation but inhibits cellular differentiation, apoptosis, 7 and angiogenesis. 8 In mice, lack of mature podocyte miRs induces marked proteinuria and glomerular and tubular injury. Furthermore, glomerular miR-26a expression implies a possible role in preservation of glomerular filtration barrier function.…”
mentioning
confidence: 99%